(Non-)linear stiffness customisation of metallic additive manufactured springs. Issue 1 (31st December 2023) - Danun, Aschraf N.; Poole, Oliver; Tarter, Edouard; Beutler, Patrick; Meboldt, Mirko
ABSTRACT: Additive manufacturing (AM) facilitates the fabrication of compliant mechanisms through its free-form and design customisation capabilities. Specifically, the properties of kinetic mechanisms such as springs can be extended with regards to their inherent (non-)linear stiffness functions. This allows for the customisation of AM springs according to user preferences. By combining the design synthesis approach of building blocks with the structural optimisation approach for AM, it is possible to define and customise spring stiffness functionalities. The optimisation process employs an automated computational framework based on a genetic algorithm scheme, which has been demonstrated through randomised and reference case studies. This framework enables the attainment of linear, progressive (stiffening), and degressive (softening) stiffness curves. The manufacturability of the springs has been validated through laser powder bed fusion using stainless-steel material 17–4 PH (H900). The springs have resulted in an accuracy error of maximum 6.48% and precision error of maximum 5% through compression testing.